ANALYSIS OF THE IMPACT OF THE GULF WAR ON INDONESIA’S ECONOMIC STABILITY: IBN KHALDUN’S PERSPECTIVE - Zakki Afin; Syaiful Anam (Assets Journal: Journal of Economic and Business, 2026)
This research aims to analyze the impact of the Gulf War on Indonesia's economic stability from the perspective of Ibn Khaldun's thought. The Gulf War is an international conflict that has a major impact on global economic conditions, especially on the international trade sector, world oil prices, inflation, and financial market stability. As part of the global economic system, Indonesia is also affected by this geopolitical instability. This research uses a qualitative approach with the type of library research. The data source is obtained from Ibn Khaldun's main work, namely Muqaddimah, as well as various previous journals, books, and research relevant to the Gulf War and Indonesia's economic stability. The data collection technique is carried out through a documentation study, while the data analysis technique uses a descriptive-analytical method. The results of the study show that the Gulf War had an impact on Indonesia's economic stability through the increase in world oil prices, increasing inflation, disruption of international trade, and fluctuations in the rupiah exchange rate. In Ibn Khaldun's perspective, conflicts and wars can lead to weakening economic activity, disruption of trade, and declining public welfare due to political and security instability. Ibn Khaldun's thoughts on the relationship between political stability and economic prosperity are still relevant to explain contemporary economic phenomena. This study concludes that international geopolitical conflicts have a great influence on national economic stability. Therefore, it is necessary to strengthen domestic economic resilience, political stability, and government policies oriented towards the welfare of the people in facing the impact of the global crisis.